Reconstructing National Integration Values through Critical Literacy in English Language Learning in Higher Education - Inesensia Jesika Tiwe; Tasya Polin; Anastasya Suryani Dewintari; Lodia Mone; Dian Saskia Awang; Afret Benu; Tans Feliks (Peneliti.net, 2026)
he development of globalization and digital media has had a significant impact on the mindset and character of young generations, including the declining awareness of national integration values. Higher education institutions have a strategic role in reconstructing the values of unity, tolerance, and national identity through critical and reflective learning processes. This study aims to describe the reconstruction of national integration values through the implementation of critical literacy in English language learning at the tertiary education level. The study employed a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation of the English language learning process. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that the critical literacy approach is capable of enhancing students’ critical thinking skills in understanding texts, analyzing social and cultural issues, and connecting global discourses with Indonesian national values. In addition, students demonstrated increased awareness of the importance of tolerance, diversity, unity, and social responsibility in community life. The implementation of critical literacy in English language learning is not only oriented toward the mastery of language competencies but also serves as a means of character development and the strengthening of national integration within higher education environments. Therefore, this approach can serve as an alternative pedagogical strategy in supporting character education and strengthening national insight in the era of globalization.